So we have (5x - 11)/(2x^2 + x - 6) = A/(x + 2) + B/(2x - 3)

We can go several ways, but they are all amount to the same thing. I'll use the way that requires less typing, tell me if you dont understand something.

Multiply the equation through by (x + 2)(2x - 3), we obtain:

5x - 11 = A(2x - 3) + B(x + 2)

=> 5x - 11 = 2Ax - 3A + Bx + 2B

By grouping like powers of x, we obtain

=> 5x - 11 = (2A + B)x + (2B - 3A)

Now we equate the coefficients of like powers of x on both sides of the equation, we get:

2A + B = 5 .........................(1)

-3A + 2B = -11 ...................(2)

We solve these simultaneous equations to obtain A and B, I think you can take it from here